STRATEGI KOMUNIKASI PEMASARAN PELAKU USAHA MIKRO PENERIMA PROGRAM PAHLAWAN EKONOMI NUSANTARA DI KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG - Diana Diana; Evi Nurhayati (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial, 2026)
The government has issued an empowerment policy aimed at increasing incomes and eliminating dependence on social assistance through the Pahlawan Ekonomi Nusantara (PENA) program, which includes business assistance, training, and mentoring. Many micro-entrepreneurs receiving the PENA program in North Sumedang District do not yet understand the importance of clear, consumer oriented marketing communication planning, such as the message delivered, the selection of marketing communication media and digital media to reach consumers widely and efficiently. This study examines how micro-entrepreneurs beneficiaries of the PENA program develop effective marketing communications through eight steps of effective marketing communication (Integrated Marketing Communication). This study used a descriptive qualitative method to gain in-depth understanding of marketing communication strategies. Informants in this study consisted of three PENA program beneficiaries, three consumers, and three social facilitators. Data collection techniques included observation, in-depth interviews, and documentation studies. The results indicate that micro-entrepreneurs determine communication targets based on geographic proximity, psychographics, social relationships, and consumer roles. Communication objectives are directed toward supporting business goals, and messages are designed effectively. Although micro-enterprises do not allocate a specific budget for marketing communications, they simply yet integratedly combine personal communications, digital media, sales promotions, and print media, tailored to consumer characteristics. Measuring promotional results reflects the stages of the AIDA model and the Hierarchy of Effects, where success is measured not only by sales but also by consumer awareness, interest, desire, and action. Furthermore, feedback in marketing communications is simple, effective, and relevant to the characteristics of micro-enterprises, even though it has not been systematically planned. KEYWORDS: Marketing Communication Strategy, Micro-Enterprises, Nusantara Economic Heroes Program